Here, there and everywhere: a study of consumer centrism - Prince, Melvin; Davies, Mark; Cleveland, Mark; Palihawadana, Dayananda (International Marketing Review, 2016)
Purpose - A first objective is to add insight into how constructs of ethnocentrism, xenocentrism and cosmopolitanism relate to each other. Knowledge of how these constructs overlap or work together in affecting consumer preferences will offer global marketers insights for designing appropriate marketing strategies. The second objective is to extend this knowledge by examining the correspondence of these three constructs to a nomological network of dispositional concepts pertinent for product positioning and market segmentation. The third objective is to empirically examine the extent to which the measures, construct structure and associative relationships are robust in different national research settings. The paper aims to discuss these issues. Design/methodology/approach - Surveying British and American consumers, this study examines and analyzes the correspondence of these identity-relevant constructs within a nomological net of pertinent concepts: consciousness-of-kind, global consumption orientation, materialism and natural environment concern. Findings - The hypothesized negative links between CET-XEN and CET-COS, and the predicted positive connection between XEN-COS were all confirmed on the latent factor results for the combined data set. The negative correlation between CET-XEN was of a considerably lower magnitude than that for CET-COS. Originality/value - To date, no research has used an identity theory framework and simultaneously examined in a cross-cultural context the interrelationships of consumer ethnocentrism consumer xenocentrism and cosmopolitanism - and their differentiating linkages to a multiplicity of consumer dispositions.
43 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/102-838-974-401-396 tex.type: [object Object]
Keywords: Cross-cultural studies; Ethnocentrism; Global marketing; Green issues; Market segmentation; Marketing; dept.mkt; peer-reviewed